2022
DOI: 10.1292/jvms.22-0073
|View full text |Cite
|
Sign up to set email alerts
|

Stress decreases contraction of the colon, and the effects of stress are different among the regions of the colon

Abstract: Stress affects a variety of organs. Diarrhea and constipation are closely related to stress, which involves the gastrointestinal motility of the colon. We compared the gastrointestinal motility of the proximal, mid, and distal colon in mice with stress. Stress was applied by water immersion restraint. Colon motility was measured using an isotonic transducer in the direction of the circular muscles. Electric field stimulation-induced contractions in stressed mice were reduced compared to control mice in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Our findings were supported by previous studies in which stress altered the gastrointestinal (GI) motility and induced changes in the secretions, intestinal barrier permeability, and gut microbiota [7]. A study on mice subjected to water-immersion stress reported a reduction in longitudinal contractions of both the proximal and distal colon [19]. Restrained C57BL/6 mice exhibited a diarrhea-like phenotype by increased motility [20].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings were supported by previous studies in which stress altered the gastrointestinal (GI) motility and induced changes in the secretions, intestinal barrier permeability, and gut microbiota [7]. A study on mice subjected to water-immersion stress reported a reduction in longitudinal contractions of both the proximal and distal colon [19]. Restrained C57BL/6 mice exhibited a diarrhea-like phenotype by increased motility [20].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that colon length was reduced in mice with increased stress (Ono et al, 2022) and colitis (Ren et al, 2011;Wen et al, 2013;Zhang et al, 2018b). Thus, we investigated the correlation between oxidative stress and ASD modeling by estimating intracellular ROS levels in the blood cells using ROSsensitive dye, DCFH-DA, with full wavelength fluorometric enzyme labeler, for three consecutive days after inducing SD.…”
Section: Sx Alleviates Asd-induced Oxidative Stressmentioning
confidence: 99%
“…With regard to the underlying molecular and neurochemical changes of the neuromuscular apparatus, studies in mice have shown that chronic water immersion stress (3 h, 7 days and 13 days) reduced colonic and ileal contractions (Azuma et al., 2021; Ono et al., 2022). Additionally, chronic water‐avoidance stress (1 h, 9 days) increased spontaneous and inhibitory junction potentials in the colon (Reed et al., 2016), thereby increasing inhibitory neuromuscular transmission.…”
Section: The Stress Response: From Adaptation To Diseasementioning
confidence: 99%